O uso do óleo essencial de lavanda para crianças com TEA: estudo de caso sobre o impacto na qualidade do sono e ansiedade - Velez, Stephanie Helen Ribeiro (2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that is characterized by difficulties in social communication and by restricted behaviors and repetitive activities. Therefore, one of the main difficulties of children with ASD is related to the action of falling asleep and staying asleep, with nocturnal awakening having a strong association with daytime behavior problems. In this sense, considering the need to intervene to minimize the level of anxiety in these children in order to provide an environment that promotes a more peaceful and restorative sleep, as well as the need for these children to access Integrative and Complementary Health Practices in the SUS in order to provide an integrative and complementary therapy to the medications used in the treatment of ASD, the present study aimed to apply the Protocol for the Use of Lavender Essential Oil for Children with ASD and to identify its effect on the sleep and behavior of two children in the municipality of Currais New/RN. Two children were selected considering the following inclusion criteria: children aged between 6 and 12 years old with a clinical diagnosis of ASD and with a sleep disorder, mothers or guardians of children with ASD who wish to participate in the study voluntarily by signing the TCLE , children who accept the use of lavender essential oil. Exclusion criteria were: children who have autistic traits, but who do not have diagnostic confirmation, children using psychotropic drugs or other sleep inducers, children who have other deficiencies or associated diseases. The results were obtained from the description of the mothers' field diary in the application of the protocol. The analysis of the cases was carried out based on the evaluation of the testimonies of the mothers recorded in the diary associated with the categories: time to fall asleep, episodes of anxiety during the day, sensory hyper-reactivity, quality of the mother-child relationship and change of routine. Despite the limitations of the study, it does not allow us to state that the benefits of applying the protocol are associated only with the use of lavender essential oil, both children obtained a significant improvement in the act of falling asleep and staying asleep, reduced anxiety and irritability, and greater concentration during the activities of daily living.